2005
DOI: 10.1242/dev.02019
|View full text |Cite
|
Sign up to set email alerts
|

Temporally controlled targeted somatic mutagenesis in embryonic surface ectoderm and fetal epidermal keratinocytes unveils two distinct developmental functions of BRG1 in limb morphogenesis and skin barrier formation

Abstract: Animal SWI2/SNF2 protein complexes containing either the brahma (BRM) or brahma-related gene 1 (BRG1) ATPase are involved in nucleosome remodelling and may control the accessibility of sequence-specific transcription factors to DNA. In vitro studies have indicated that BRM and BRG1 could regulate the expression of distinct sets of genes. However, as mice lacking BRM are viable and fertile, BRG1 might efficiently compensate for BRM loss. By contrast, as Brg1-null fibroblasts are viable but Brg1-null embryos die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 35 publications
(46 reference statements)
5
122
0
Order By: Relevance
“…Our data indicate that the loss of both BRG1 alleles induces apoptosis in non-transformed lung epithelial cells. BRG1 is required for the establishment and maintenance of epithelial polarity (Indra et al, 2005), an observation that is consistent with both the pro-apoptotic effects of BRG1 knockout in the lung as well as with the early embryonic lethality of BRG1 knockout in mice. On the other hand, knockout of both BRG1 alleles in urethane-induced tumors promotes tumorigenesis (Glaros et al, 2008).…”
Section: Transgenic Knockout Of Brm or Brg1 Enhances Transformationsupporting
confidence: 70%
See 1 more Smart Citation
“…Our data indicate that the loss of both BRG1 alleles induces apoptosis in non-transformed lung epithelial cells. BRG1 is required for the establishment and maintenance of epithelial polarity (Indra et al, 2005), an observation that is consistent with both the pro-apoptotic effects of BRG1 knockout in the lung as well as with the early embryonic lethality of BRG1 knockout in mice. On the other hand, knockout of both BRG1 alleles in urethane-induced tumors promotes tumorigenesis (Glaros et al, 2008).…”
Section: Transgenic Knockout Of Brm or Brg1 Enhances Transformationsupporting
confidence: 70%
“…RNAimediated knockdown of BAF60 in embryonic stem cells inhibits cardiovascular morphogenesis (Lickert et al, 2004). A dominant-negative BRG1 allele blocks myeloid differentiation of 32Dcl3 cells (Vradii et al, 2006), whereas loss of BRG1 in keratinocytes results in defects in limb patterning (Indra et al, 2005). Studies in embryonic stem cells have revealed that lack of BAF250 can compromise cell pluripotency and severely inhibit self-renewal, whereas functional BAF250 contributes to the proper expression of numerous genes involved in embryonic stem cell self-renewal, including Sox2, Utf1 and Oct4 (Yan et al, 2008) (Gao et al, 2008).…”
Section: The Swi/snf Complex Is Involved In Differentiationmentioning
confidence: 99%
“…Loss of expression of Brg1 and Brm in the epidermis does not considerably affect proliferation, but does lead to aberrant expression of differentiation genes and results in defective formation of the skin barrier (Table 1) (Indra et al 2005). This is consistent with the known role of SWI/SNF in mediating exit from cell cycle in combination with Rb and HDAC (Zhang et al 2000).…”
Section: Chromatin Remodeling By Swi/snfsupporting
confidence: 72%
“…In order to achieve conditional inactivation of Brg1 in the small intestinal epithelium, we crossed mice expressing Cre-ER T2 recombinase under control of the Villin 1 promoter (Vil1) (Tg(Vil-cre/ESR1)23Syr, further abbreviated as VillinCreER T2 ) [20] to animals carrying loxP-flanked alleles of Brg1 [21,22]. The Cre-ER T2 encodes a fusion protein between the Cre recombinase and mutated estrogen receptor and is activated by exposure to tamoxifen.…”
Section: Brg1 Loss Compromises Stem Cell Maintenance In the Murine Smmentioning
confidence: 99%